Student Perception of the Effectiveness of the Storytelling Method in English Learning: Quantitative Research with a Focus on Reading Skills - Hariadi Syam; Iin Almeina Loebis; Neng Nurwiatin; Mansyur Srisudarso; Defi Irwansyah (Yayasan Adra Karima Hubbi, 2024)
Background. The storytelling method has become a popular approach in English language learning due to its ability to increase student interest and participation. However, quantitative research specifically focussing on the effectiveness of this method in the development of reading skills is limited. Purpose. This study aims to investigate students' perceptions of the effectiveness of the storytelling method in English language learning, with a focus on the development of reading skills. Method. This study uses a quantitative approach by distributing questionnaires to students who are learning English. The questionnaire measured students' perceptions of the effectiveness of the storytelling method in improving their reading skills. Results. The results showed that most students (83.3%) believed that the storytelling method was effective or very effective in improving their interest and understanding of reading skills. However, a small proportion of students (16.7%) had a neutral view on the effectiveness of this method. Conclusion. The findings of this study indicate that the storytelling method is effective in improving students' reading skills in English language learning. By considering students' perceptions and integrating the storytelling approach into the curriculum, educators can enhance students' learning experiences and support the development of reading skills more effectively.